2004
DOI: 10.1176/appi.ajp.161.5.836
|View full text |Cite|
|
Sign up to set email alerts
|

A Randomized, Placebo-Controlled Trial of Sertraline for Prophylactic Treatment of Highly Recurrent Major Depressive Disorder

Abstract: Among remitted patients with a history of multiple depressive episodes, sertraline at a dose of either 50 or 100 mg/day prevented recurrences significantly more than did placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 18 publications
0
29
0
6
Order By: Relevance
“…In total, the authors had reported in 65 papers on various studies of antidepressant maintenance trials, but 36 of these had not documented suicides or suicide attempts or had not provided data upon request. The following 29 studies were included in our quantitative analysis: Blumenthal et al [30], Cheung et al [31], Doogan and Caillard [32], Emslie et al [33], Feiger et al [34], Goodwin et al [35], Kamijima et al [36], Kishimoto et al [37], Klysner et al [38], Kornstein et al [39], Lepine et al [40], Licht et al [41], Lustman et al [42], McGrath et al [43], Montgomery et al [44], Montgomery and Dunbar [45], Old Age Depression Interest Group [46], Perahia et al [47], Reynolds et al [48], Robinson et al [49], Rosenthal et al [50], Rouillon et al [51], Schmidt et al [52], Shiovitz et al [53], Stewart et al [54], Terra and Montgomery [55], Thase et al [56], Versiani et al [57], Weihs et al [58]. …”
Section: Resultsmentioning
confidence: 99%
“…In total, the authors had reported in 65 papers on various studies of antidepressant maintenance trials, but 36 of these had not documented suicides or suicide attempts or had not provided data upon request. The following 29 studies were included in our quantitative analysis: Blumenthal et al [30], Cheung et al [31], Doogan and Caillard [32], Emslie et al [33], Feiger et al [34], Goodwin et al [35], Kamijima et al [36], Kishimoto et al [37], Klysner et al [38], Kornstein et al [39], Lepine et al [40], Licht et al [41], Lustman et al [42], McGrath et al [43], Montgomery et al [44], Montgomery and Dunbar [45], Old Age Depression Interest Group [46], Perahia et al [47], Reynolds et al [48], Robinson et al [49], Rosenthal et al [50], Rouillon et al [51], Schmidt et al [52], Shiovitz et al [53], Stewart et al [54], Terra and Montgomery [55], Thase et al [56], Versiani et al [57], Weihs et al [58]. …”
Section: Resultsmentioning
confidence: 99%
“…The unadjusted frequency of relapse was 22% for active treatment, compared with 42% for placebo. An additional 11 RCTs were 1 year or longer (28,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). These trials also provide consistent evidence in favor of active treatment over placebo, with the majority representing recurrence prevention during maintenance-phase treatment.…”
Section: Placebo-controlled Trialsmentioning
confidence: 88%
“…Trials 1 year or longer-Eleven trials provided data points for followup of 1 year or more ( Figure 2): one on citalopram (28), one on escitalopram (38), one on fluvoxamine (30), one on nefazodone (31), two on paroxetine (32,37), four on sertraline (33)(34)(35)39), and one on venlafaxine (36). Trials consistently favored active treatment over placebo for preventing relapse and/or recurrence, although differences were not always statistically significant.…”
Section: Meta-analysismentioning
confidence: 99%
“…Otherwise, the rates were extracted from the survival graph figures in the original reports. All of the studies satisfied the 24 week time point, 9 out of 11 studies satisfied the 48 week time point (Gilaberte et al, 2001;Hochstrasser et al, 2001;Keller et al, 1998;Klysner et al, 2002;Kocsis et al, 2007;Kornstein et al, 2006;Lepine et al, 2004;McGrath et al, 2006;Perahia et al, 2006;Reynolds et al, 1999;Sackeim et al, 2001), 4 out of 11 studies satisfied the 72 week time point (Hochstrasser et al, 2001;Keller et al, 1998;Lepine et al, 2004;Reynolds et al, 1999) and only 1 study satisfied the 96 week time point (Reynolds et al, 1999) (Figure 1). …”
Section: Information Retrievalmentioning
confidence: 98%
“…A different approach is to only randomize those patients who had not experienced a relapse after 2 months of masked placebo treatment. By doing so, the study selects for only the patients in remission and not those whose prophylactic therapy is masking an underlying, unremitting depression (Lepine et al, 2004).…”
Section: Introductionmentioning
confidence: 99%